2019
DOI: 10.5194/acp-19-13017-2019
|View full text |Cite
|
Sign up to set email alerts
|

On what scales can GOSAT flux inversions constrain anomalies in terrestrial ecosystems?

Abstract: Abstract. Interannual variations in temperature and precipitation impact the carbon balance of terrestrial ecosystems, leaving an imprint in atmospheric CO2. Quantifying the impact of climate anomalies on the net ecosystem exchange (NEE) of terrestrial ecosystems can provide a constraint to evaluate terrestrial biosphere models against and may provide an emergent constraint on the response of terrestrial ecosystems to climate change. We investigate the spatial scales over which interannual variability in NEE c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 78 publications
2
26
0
Order By: Relevance
“…To a large extent, IAV in the carbon balance of ecosystems is expected to be driven by IAV in temperature and moisture (Berry & Bjorkman, 1980; Byrne et al, 2019; Smith et al, 2011); thus, we examine the relationship between CO 2 flux anomalies and anomalies in soil temperature (ΔT) and soil moisture (ΔM). Figure 4 shows the correlation between ΔGPP and anomalies in climate variables over 2001–2017.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To a large extent, IAV in the carbon balance of ecosystems is expected to be driven by IAV in temperature and moisture (Berry & Bjorkman, 1980; Byrne et al, 2019; Smith et al, 2011); thus, we examine the relationship between CO 2 flux anomalies and anomalies in soil temperature (ΔT) and soil moisture (ΔM). Figure 4 shows the correlation between ΔGPP and anomalies in climate variables over 2001–2017.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, space‐based measurements of column‐averaged dry‐air mole fractions of CO 2 ( normalXCO2) have allowed for much expanded observational of coverage, leading to top‐down NEE constraints on smaller spatial scales (Bowman et al, 2017; Byrne et al, 2017, 2019, 2020; Guerlet et al, 2013; Ishizawa et al, 2016; Liu et al, 2017; Liu, Bowman, Parazoo, et al, 2018). Furthermore, advances in remote sensing techniques have allowed for more reliable GPP estimates from space from solar‐induced fluorescence (SIF) measurements (Byrne et al, 2018; Frankenberg et al, 2011; Joiner et al, 2011; Parazoo et al, 2014; Sun et al, 2017; Yang et al, 2015) and up‐scaled flux tower GPP estimates using MODIS observations (Joiner et al, 2018; Jung et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that neither CO 2 advection nor the light inhibition of leaf respiration appears to generate sizable biases of global GPP in FLUXCOM -a tendency likely encouraged by the relatively strict quality control on the EC flux data (Tramontana et al, 2016). Furthermore, a comparison of EC-based GPP with biometric GPP estimates across 18 globally distributed sites showed good agreement and no significant bias (Campioli et al, 2016). A recent study using partitioning based on carbonyl sulfide (COS) for four contrasting European sites also showed good agreement with standard EC-based GPP where systematic differences for mean GPP were < 5 % (Spielmann et al, 2019).…”
Section: Mean Annual Gross Primary Productivitymentioning
confidence: 98%
“…This is likely due to (1) a combination of sparse satellite data availability, cloud contamination and geometrical illumination effects in the tropics or (2) that the processes governing NEE IAV in the tropics cannot be captured by satellitebased predictors alone in RS (even under ideal observational conditions) but require additional meteorological variables such as temperature that are included in the RS+METEO setup. Some support for the latter point comes from Byrne et al (2019), who found strong correlations of anomalies from GOSAT inversions with NEE from RS+METEO and soil temperatures in the tropics but not with SIF and a drought indicator, suggesting that temperature impacts respiration more than photosynthesis in the tropics.…”
Section: Interannual Variability Of Net Ecosystem Exchangementioning
confidence: 99%
“…From the top‐down, measurements of the atmospheric CO 2 can provide constraints on net ecosystem exchange (NEE)—the net exchange of CO 2 between an ecosystem and the atmosphere, determined as autotrophic and heterotrophic respiration minus GPP (Bolin & Keeling, ; Gurney et al, ; Yin et al, ). Space‐based measurements of column‐averaged dry‐air mole fractions of CO 2 (X CO2 ) have been shown to provide information on NEE anomalies at large subcontinental scales (Byrne et al, ; Byrne et al, ; Guerlet et al, ; Ishizawa et al, ; Liu, Bowman, et al, ; Liu et al, ; Yin et al, ) and for point sources (Nassar et al, ; Schwandner et al, ) but are untested on smaller regional scales, such as the Midwest croplands. The Orbiting Carbon Observatory 2 (OCO‐2), launched in 2014, provides X CO2 to monitor the atmospheric signal of the event.…”
Section: Introductionmentioning
confidence: 99%